Dampak Kebijakan Denda Okupasi Lahan PT KAI terhadap Warga Permukiman Informal di Sugihwaras, Madiun - Bayu Aji Sastra Jendra; Bintarsih Sekarningrum; Desi Yunita (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
The land occupation fine policy imposed by PT Kereta Api Indonesia (PT KAI) is formally presented as part of asset regulation and optimization. Yet its implementation has generated significant tension among long-established residents living in informal settlements on PT KAI–owned land. The lack of public participation, procedural transparency, and sensitivity to local socio-economic realities has intensified uncertainty and vulnerability within the community. This study examines the impact of the fine policy on residents of Wadukan Hamlet in Sugihwaras Village, Saradan District, Madiun Regency, using a descriptive qualitative approach supported by literature review and field interviews. Drawing on Antonio Gramsci’s concept of hegemony, the study explores how administrative instruments function as mechanisms of symbolic power and spatial control. The findings show that residents recognize PT KAI’s legal ownership and have long contributed through informal dues; however, the sudden escalation of fines and the marking of homes without adequate socialization have produced economic burdens, psychological distress, and a heightened sense of insecurity. What began as an administrative procedure has evolved into a form of structural marginalization. The study underscores the need for policy reform grounded in social justice, transparent implementation, and meaningful community engagement so that state spatial governance does not operate as a vehicle of exclusion.